Sustainable use of Agrochemicals: A Review - Mondal, Naba K.; Dey, Uttiya; Das, Kousik; Datta, Jayanta K. (Indian Science Cruiser, 2012)
Agrochemicals are added to the fanning systems to improve production[l]. They include pesticides and fertilizers which ’stimulate or regulate the growth of or control pests of, agriculture, horticulture or plantation crops, and of domesticated livestock. The origin and concept, known exactly, of pesticide is not known. Pesticides or insecticides are among the most extensively used chemicals in the world today and they are also the most hazardous compounds to the human being as well.